2021
DOI: 10.38212/2224-6614.3347
|View full text |Cite
|
Sign up to set email alerts
|

Application of a comprehensive metabolomics approach for the selection of flaxseed varieties with the highest nutritional and medicinal attributes

Abstract: Flaxseed is considered an indispensable generally recognized as safe (GRAS) source of polyphenolic lignans, polyunsaturated fatty acids (PUFA), fibers as well as minerals and vitamins. The metabolite content of flaxseed reflects its nutritional and medicinal value. Therefore, the selection of flaxseed variety for food industry is dependent on its metabolome. A metabolomics approach based on liquid or gas chromatography coupled to mass spectrometry has been applied to discriminate different flaxseed cultivars t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 48 publications
1
3
1
Order By: Relevance
“…Perhaps, some part of the Xyl and Glc is accounted for xyloglucan. Contrary to our results, Salem et al [ 43 ] in flax metabolom analysis were able to identify a high content of Rha , Fuc as well as Xyl , however, Ara was not detected. The leaders in content, as in our experiment, were Raf and Suc , but in comparison with them, the level of Mylib was two orders of magnitude lower.…”
Section: Resultscontrasting
confidence: 99%
See 4 more Smart Citations
“…Perhaps, some part of the Xyl and Glc is accounted for xyloglucan. Contrary to our results, Salem et al [ 43 ] in flax metabolom analysis were able to identify a high content of Rha , Fuc as well as Xyl , however, Ara was not detected. The leaders in content, as in our experiment, were Raf and Suc , but in comparison with them, the level of Mylib was two orders of magnitude lower.…”
Section: Resultscontrasting
confidence: 99%
“…Salem et al [ 43 ] in flax metabolomic analysis showed approximately the same ratio of basic polyatomic alcohols as it occurred in our experiment, when glycerol, galtl , mInosl (and possibly Inosl similar to it) showed order of magnitude greater amounts than erythl and xylt . They did not identify mannitol and its stereoisomer dultl , but isolated their stereoisomer sorbitol.…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations